2003
DOI: 10.1021/bi020606v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dehydration on Light-Induced Reactions in Photosystem II:  Photoreactions of Cytochrome b559

Abstract: The effect of dehydration on the reaction pattern of photosystem II (PS II) has been studied by measuring and analyzing spectral changes induced by continuous wavelength illumination in films of untreated and hydroxylamine-washed PS II membrane fragments dehydrated to different levels. The obtained data revealed (i) the extent of light-induced formation of about one Q(A)(-*)per 230 chlorophylls (Chl) remains virtually invariant to dehydration down to the lowest values of relative humidity (6-8% RH); (ii) a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 114 publications
3
28
0
Order By: Relevance
“…Our DFT results suggest that redistribution of charges in the Q A Ϫ Fe(histidine) 4 Likely, there are further changes in the extended H-bonded network around the Q A FeQ B site (52-54), which could not be explicitly included in this investigation because of limited structural information from crystallography. Removal of critical water molecules may explain the blockage of Q A Ϫ 3 Q B ET after dehydration of reaction centers (55,56). Further studies are required to clarify whether a spin state change of Fe(II) parallels the coordination change.…”
Section: Discussionmentioning
confidence: 99%
“…Our DFT results suggest that redistribution of charges in the Q A Ϫ Fe(histidine) 4 Likely, there are further changes in the extended H-bonded network around the Q A FeQ B site (52-54), which could not be explicitly included in this investigation because of limited structural information from crystallography. Removal of critical water molecules may explain the blockage of Q A Ϫ 3 Q B ET after dehydration of reaction centers (55,56). Further studies are required to clarify whether a spin state change of Fe(II) parallels the coordination change.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with the QENS data of PS II membrane fragments suggests that there is a close correlation between the thermal activation of molecular dynamics and the electron transfer efficiency from Q A to Q B [10,13]. At the same time, the suppression of molecular dynamics upon dehydration [10,11,13] seems to be responsible for the inhibition of Q A to Q B electron transfer below 45% r.h. [7].…”
Section: Qens Studies Of Ps II Membranesmentioning
confidence: 99%
“…For example, the light-induced primary charge separation remains fully functional even at very low temperatures, while the Q A → Q B electron transfer is completely inhibited below about 200 K [6] and below a hydration of 45% relative humidity (r.h.) [7]. Likewise, individual reaction steps of the water oxidizing complex possess a Corresponding author: pieper@ut.ee a characteristic dependence on temperature (see [1] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the optical properties of PSII membrane fragments remain unaltered if dehydrated as thin films (Kaminskaya et al 2003). Hence the change in the optical path length of light is unlikely to affect the absorbance changes at 830 nm in measurements with dried thalli.…”
Section: P700 Absorbance Changesmentioning
confidence: 99%